The Influence of the Educational Environment on Students' Interest in Learning in Science Subjects at Junior High School: Pengaruh lingkungan pendidikan terhadap minat belajar siswa pada mata pelajaran IPA di SMP - Chilmi Muzakki; Nur Efendi (Academia Open, 2021)
This study aims to determine the effect of the educational environment on students' interest in learning. The non-experimental quantitative research method with descriptive correlational research design was tested on several experimental classes using an assessment instrument in the form of giving a questionnaire of 20 questions to determine the effect of the educational environment on students' interest in learning. The population used was 412 using simple random sampling technique so that in class VII there were 24 representatives from 119 students, class VIII 24 from representatives of 122 students, and class IX consisted of 34 representatives from 171 students at Avisena Junior High School. Data analysis used correlation between variables X and Y through the SPSS 25 application, namely. Based on the results of descriptive analysis found that the educational environment was in the good category 46.9%, and the results of interest in learning were in the good category 43.3%. The educational environment is significantly and positively related, shown because the significance value is 0.02 < 0.05, then it is correlated and the Pearson correlation value is 0.319 > 0.213 r table so that based on the correlation value greater than r table, there is a relationship between the educational environment variable and students' interest in learning science